DESARROLLO CULTURAL Y PRINCIPALES CARACTERISTICAS ARQUITECTÓNICAS EN LOS SITIOS PREHISPANICOS DEL DISTRITO DE SAN PEDRO DE LARCAY, PROVINCIA SUCRE, DEPARTAMENTO AYACUCHO - Mallco Huarcaya, Rafael (2017)
This article is a synthesis of the results of research work carried out during the years 2008 and 2009 in the area of the district of San Pedro de Larcay, which provided the documentation about 29 archaeological sites corresponding to different periods of cultural occupation, these works, indicate that the valley Chicha - Soras and its principal tributaries constituted a very important area where pre-Hispanic societies developed from the Formative Period until the Late Horizon Period. In the course of this time, societies that settled in these areas had their own forms of organization and development, production of pottery, architectural features and different forms of domain and use geographical, aspects of which by the way are own and distinctive from each other and allowed us to identify cultural of each one of the archaeological sites filiation.